Bartter Type 4a Syndrome Diagnosed in a 30-week-old Preterm Neonate - Çağrı Cumhur Gök; Özge Kaynar; Leyli Şentürk; Emrah Can; Şahin Hamilçıkan (Bagcilar Medical Bulletin, 2023)

(untitled)
Bartter syndrome is an uncommon autosomal recessive, salt-losing renal tubular disease. Its defining features are numerous electrolyte abnormalities, including low potassium and chloride levels, metabolic alkalosis, and low or normal blood pressure. We reported a case of neonatal Bartter syndrome presenting with severe hypokalemia, hypochloremic metabolic alkalosis, polyuria, and renal failure in a 28-week premature born to consanguineous parents. She was successfully treated with oral indomethacin and potassium supplements. Genetic tests were resulted in Bartter syndrome Type 4a with mutations in the BSND gene.